Need for women-centered treatment for substance use disorders: results from focus group discussions - Natasha Elms; Kendra Link; Adam Newman; Susan B. Brogly; for the Kingston House of Recovery for Women and Children (BMC, 2018)
Abstract Background There are few women-centered treatment programs for substance use disorder. We therefore undertook an exploratory study to better understand the treatment experience, barriers, and facilitators of mothers with substance use disorder. Methods We conducted two focus groups with a total of ten women with a history of substance use disorder in Kingston (Canada). Women were recruited from a community program for mothers with substance use disorder. The focus groups were recorded, and the resulting data were transcribed, coded, and thematically analyzed. Barriers, facilitators and treatment needs were identified. Results The mean age of the participants was 31.1 years, 30% were currently using substances, and 60% had a child in their care. A key concern for women regarding substance use treatment was the welfare of their child(ren). Agencies charged with child protection were a barrier to treatment because women feared disclosing substance use would result in loss of child custody. In contrast, when agencies stipulated that women must attend treatment to retain custody, they facilitated treatment engagement. Other barriers to treatment included identifying treatment programs and completing admission requirements, wait times, counselor ability to address woman-centered issues, fear, safety, and stigma. Women's personal motivation for treatment was a facilitator. Suggestions to improve treatment programs included to allow children to accompany their mothers, involvement of peer support, and women-only programs. Conclusions This small but novel study provides important data to inform treatment programming for mothers with substance use disorders.